Individual glow bands of Mn²⁺ ions photoluminescence in plastically deformed ZnS single crystals - Prokofiev, T.A.; Kovalenko, A.V.; Polezaev, B.A.; Bulanyi, M.F.; Gorban, A.A.; Hmelenko, O.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
The spectra of a photoluminescence (PL) in plastically deformed (PD) ZnS:Mn single crystals are investigated. It is shown that the PD processes cause change of a quantitative ratio between separate types of glow manganese centres (MC) as a result of their local symmetry rearrangement. After decomposing of PL integral spectra by individual PL bands using the cumulative distribution Gauss function, the nature of a ratio change between PL MC of different types is established. The individual with the peaking in the range 618-620 nm is discovered.